PENDEKATAN ACCELERATED LEARNING DALAM PEMBELAJARAN QIRA’AH - Muhamad Fathoni (STAI Masjid Syuhada Yogyakarta, 2015)
Accelerated learning is a learning approach concerning with student psychology in their learning. It is a concept based on a finding of a Bulgarian psychiatrist, Dr. George Lozanov. Lozanov says that human brain, a main learning tool, can be effectively used only when it is